Implemetasi Pada Guru/Pegawai di SMA Negeri 12 Pekanbaru Dengan Metode Tes Uji Rinne Pada Remaja Gangguan Pendengaran Dengan Penggunaan Handphone - Chairil; Ratih Oktaviani (LPPM Universitas Muhammadiyah Riau, 2020)
Mobile phone is one of the developing communication tools today. The global debate and controversy regarding the health effects of cell phones continues. There are concerns that radio frequency energy (radio waves) emitted can cause health problems, especially to hearing function. The aim of the study was to find out how